Depression and it's associated factors among male-to-female transgender people in Kuantan, Pahang - Nur Diyana Md Hadis (Kulliyyah of Medicine, International Islamic University Malaysia, 2020)
Male-to-female transgender people is a marginal group of people and their health is a neglected issue. Transgender people are underserved and stigmatized. Transgender people are particularly vulnerable to mental health concerns and psychological distress. There are multiple associated and protective factors related to depression. Hence it is important to explore these factors to manage depression among transgender people. This study aims to assess the prevalence of depression and associated risk factors among male-to-female transgender people in Kuantan, Pahang. This is a mixed-method study design which involved quantitative and qualitative studies. The study was conducted among 96 male-to-female transgender people in Kuantan, Pahang. A convenient type of sampling was used as a mean of data collection. For the quantitative part, the BDI was used to assess depression among transgender people and HIV rapid test was performed to measure prevalence of HIV positive. While for the second phase, 4 focus group discussions were conducted to explore associated and protective factors of depression among male-to-female transgender people. The quantitative data was analysed using simple logistic regression to find the association between categorical data. While the qualitative data was transcribed verbatim and analysed using a thematic approach. The prevalence of depression among male-to-female transgender people in Kuantan was 37.5%. Majority of the respondents were Malays ( 82.3%), Muslims (99%), unmarried ( 93.8%) with a monthly income of <RM2300 (91.7%). The prevalence of HIV-positive in this study was 6.1%. There is no significant association between sociodemographic data of the participants and depression from the quantitative data. While from the qualitative data, 6 emerged as associated factors of depression which were (i) Family acceptance and support, (ii) discrimination and prejudice, (iii) health status, (iv) reduced self-worth, (v) challenges to change and (vi) substance use. 2 protective factors emerged from the study were (i) spirituality and (ii) good family support. Transgender people are more prone to depression as compared to the general population. Thus, it is important to screen them opportunistically. The most highlighted issue discussed from the focus group discussion was discrimination and prejudice faced by the transgender people. This was not only coming from the society, but it occurred from health care providers as well. So, we need to educate the health care providers to be non-judgemental in handling this high-risk group.